EFFECTS OF DOSAGE AND APPLICATION FREQUENCY OF FOLIAR-APPLIED MATURE COCONUT WATER ON COCOA (Theobroma cacao L.) SEEDLING GROWTH - Sri Juniati Simamora; Santi Rosniawaty; Yudithia Maxiselly (UIN Sunan Gunung Djati Bandung, 2026)
Indonesia's cocoa production has experienced instability in recent years, highlighting the need to improve productivity through intensification and extensification strategies. The success of these approaches is highly dependent on the availability of high-quality seedlings. Therefore, the utilization of coconut water as a natural plant growth regulator and supplementary nutrient source has potential to enhance cocoa seedling growth. This study aimed to evaluate the effects of different doses and application frequencies of mature coconut water applied as a foliar spray on cocoa seedling growth and to determine the most effective treatment combination. The experiment was conducted from December 2025 to May 2026 at the Ciparanje Experimental Field, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, located at an altitude of approximately 752 m above sea level. A Randomized Block Design (RBD) consisting of ten treatments and three replications was employed. Treatments comprised combinations of mature coconut water doses of 10, 15, and 20 mL plant⁻¹ applied at intervals of 7, 14, and 21 days, while a 0.2% urea treatment served as the control. Observed variables included plant height, stem diameter, and leaf number. The results showed that foliar application of mature coconut water significantly increased cocoa seedling stem diameter at 6–10 weeks after treatment. In addition, variations in coconut water dose and application frequency were able to support plant height and leaf production with effectiveness comparable to that of the inorganic fertilizer treatment (urea). For stem diameter, the application of 10, 15, and 20 mL plant⁻¹ resulted in significantly greater values than the control treatment. Among the tested application intervals, the 21-day interval was found to be the most effective.